Peran Media Pembelajaran Dalam Mengatasi Anak Hiperaktif Studi Kasus di TK RA UMDI Ujung Lare - Aldawiah, Aldawiah; Tadzkirah, Tadzkirah (PT Ininnawa Paramacitra Edukasi, 2025)
This research aims to analyze the role of learning media in overcoming learning challenges in hyperactive children at RA UMDI Ujung Lare Kindergarten. Hyperactive children often have difficulty focusing and self-control, hindering their learning process. This study uses a qualitative approach with a case study method to explore how learning media can be used as an effective tool in increasing children's attention, motivation, and involvement. The research results show that interactive and interesting learning media, such as educational games, visual aids, and sensory-based activities, have a positive impact in helping hyperactive children manage their energy and improve their learning abilities. These findings emphasize the importance of selecting appropriate learning media to create an inclusive learning environment while supporting the optimal development of the potential of hyperactive children